Subjective Birth Experience Predicts Mother–Infant Bonding Difficulties in Women With Mental Disorders - Junge-Hoffmeister, Juliane; Bittner, Antje; Garthus-Niegel, Susan; Goeckenjan, Maren; Martini, Julia; Weidner, Kerstin (Frontiers in Global Women's Health, 2022)
Background The subjective experience of giving birth to a child varies considerably depending on psychological, medical, situational, relational, and other individual characteristics. In turn, it may have an impact on postpartum maternal mental health and family relationships, such as mother–infant bonding. The objective of the study was to evaluate the relevance of the subjective birth experience (SBE) for mother–infant bonding difficulties (BD) in women with mental disorders. Methods This study used data from N = 141 mothers who were treated for postpartum mental disorders in the mother–baby day unit of the Psychosomatic University Clinic in Dresden, Germany. Patients' mental status at admission and discharge was routinely examined using a diagnostic interview (SCID I) and standard psychometric questionnaires (e.g., EPDS, BSI, PBQ). Both, the SBE (assessed by Salmon's Item List, SIL) as well as medical complications (MC) were assessed retrospectively by self-report. The predictive value of SBE, MC, as well as psychopathological symptoms for mother–infant BD were evaluated using logistic regression analyses. Results About half of this clinical sample (47.2%) reported a negative SBE; 56.8% of all mothers presented with severe mother–infant BD toward the baby. Mothers with BD showed not only significantly more depressiveness (EPDS: M = 16.6 ± 5.6 vs. 14.4 ± 6.2*), anxiety (STAI: M = 57.2 ± 10.6 vs. 51.4 ± 10.6***), and general psychopathology (BSI-GSI: M = 1.4 ± 0.7 vs. 1.1 ± 0.6**) compared to women without BD, but also a significantly more negative SBE (SIL: M = 79.3 ± 16.2 vs. 61.3 ± 22.9***). Moreover, the SBE was the most powerful predictor for BD in univariate and multiple logistic regression analyses [OR = 0.96*** (95% CI 0.94–0.98) vs. OR = 0.96** (95% CI 0.93–0.98)], even when univariate significant predictors (e.g., current psychopathology and MC during birth) were controlled. Conclusions A negative SBE is strongly associated with mother–infant bonding in patients with postpartum mental disorders. It needs to get targeted within postpartum treatment, preferably in settings including both mother and child, to improve distorted mother–infant bonding processes and prevent long-term risks for the newborn. Furthermore, the results highlight the importance of focusing on the specific needs of vulnerable women prior to and during birth (e.g., emotional safety, good communication, and support) as well as individual factors that might be predictive for a negative SBE.